Influence of the ion viscosity on the current sheet formation and plasma heating - Kurov, A.A.; Stepanov, K.N. (Вопросы атомной науки и техники, 2012)
This paper deals with the problem of the ion viscosity influence on the current sheet formation and plasma heating, in the experiments performed on “Current sheet” facility (Prokhorov General Physics Institute, Russian Academy of Sciences). On the basis of magnetohydrodynamic theory one can see that pressure force and viscid tension force can bring considerable contribution to the formation and heating of the current sheet plasma. The estimations obtained show that the effect of the ion viscosity is comparable with other effects which were taken into account previously.